2008
DOI: 10.1093/jn/138.9.1602
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, at Concentrations Attainable with Moderate Wine Consumption, Stimulates Human Platelet Nitric Oxide Production3

Abstract: The mechanisms through which moderate wine consumption reduces ischemic cardiovascular events are not yet fully unraveled. Grape extracts or a mixture of the polyphenols contained in wine were previously shown to increase nitric oxide (NO); however, little information is available on the effect of resveratrol, one of the main polyphenols of wine, on platelet NO production. We assessed the effects of resveratrol, at the concentrations attainable after moderate wine intake, on platelet NO production and the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 51 publications
(87 reference statements)
4
85
0
1
Order By: Relevance
“…Compared to placebo, our lowest dose (30mg) was shown to significantly improve FMD. A recent in vitro study (25) has shown that NO production could be enhanced in platelet cells of healthy adults after 15 days of moderate red wine consumption (300mL/day), which was associated with only a small amount of resveratrol (0.5μmol/L) in the plasma. However, other polyphenols present in the red wine may have contributed to the increased NO production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to placebo, our lowest dose (30mg) was shown to significantly improve FMD. A recent in vitro study (25) has shown that NO production could be enhanced in platelet cells of healthy adults after 15 days of moderate red wine consumption (300mL/day), which was associated with only a small amount of resveratrol (0.5μmol/L) in the plasma. However, other polyphenols present in the red wine may have contributed to the increased NO production.…”
Section: Discussionmentioning
confidence: 98%
“…The purported cardiovascular benefits of resveratrol from experimental evidence include defence against ischaemic-reperfusion injury (21)(22)(23), suppression of platelet aggregation (16,24), enhanced antioxidant status (16,25) and increased NO bioavailability through enhanced endothelial NO synthase expression in cultured human endothelial cells (14)(15). Recently, the progression of endothelial dysfunction and vascular remodelling in rats with pulmonary and cardiac abnormalities were slowed after three weeks of daily resveratrol administration (25mg/kg) (26).…”
Section: Introductionmentioning
confidence: 99%
“…Gresele et al [35] found 15 days of 300 mL wine consumption to increase plasma resveratrol concentration (total, including metabolites, precluding accurate conversion to mg/L) from 0.7270.3 to 1.3370.3 mmol/L for white wine (0.25 g polyphenols/L) and from 0.7170.2 to 1.7270.1 mmol/L for red wine (1.8 g polyphenols/ L). Red wine increased plasma resveratrol by 1.0 mmol/L, whereas white wine increased plasma resveratrol concentration by 0.6 mmol/L.…”
Section: Bioavailability From Wine and Juice Consumptionmentioning
confidence: 99%
“…The activities of various resveratrol metabolites remain an open question. Reporting of plasma resveratrol measurements has been inconsistent, with researchers employing a variety of analytical chemistry techniques, and with some reporting concentrations of resveratrol and its metabolites separately [29] and others reporting combined measurements [35]. Animal models have suggested that metabolites of resveratrol may be converted back into resveratrol at the tissue level, although this has not been rigorously demonstrated [29,42].…”
Section: Limitations To Bioavailability Researchmentioning
confidence: 99%
“…Zn and Se) as potentiators of the immune response. increased GLUT-4 expression and reduced endothelin expression and cardiac apoptosis in a genetic model of type-2 diabetes (87) ; increased insulin sensitivity caused by a decrease of the blood glucose level in mice fed a high-energy diet (88) ; attenuation of diabetic nephropathy in rats (89) ; protection of the brain from traumatic injury (90) ; inhibition of excitatory synaptic transmission in the rat hippocampus (91,92) ; neuroprotection mediated by decreased oxidative stress and increased NO release (93) . …”
Section: Conclusion and Future Perspectivementioning
confidence: 99%